Dark Classics in Chemical Neuroscience: Mescaline - Saez-Briones, P (American Chemical Society, 2018)
Archeological studies in the United States, Mexico, and Peru suggest that mescaline, as a cactus constituent, has been used for more than 6000 years. Although it is a widespread cactus alkaloid, it is present in high concentrations in few species, notably the North American peyote (Lophophora williamsii) and the South American wachuma (Trichocereus pachanoi, T. peruvianus, and T. bridgesii). Spanish 16th century chroniclers considered these cacti "diabolic", leading to their prohibition, but their use persisted to our days and has been spreading for the last 150 years. In the late 1800s, peyote attracted scientific attention; mescaline was isolated, and its role in the psychedelic effects of peyote tops or "mescal buttons" was demonstrated. Its structure was established by synthesis in 1929, and alternative routes were developed, providing larger amounts for pharmacological and biosynthetic research. Although its effects are attributed mainly to its action as a 5-HT2A serotonin receptor agonist, mescaline binds in a similar concentration range to 5-HT1A and α2A receptors. It is largely excreted unchanged in human urine, and its metabolic products are apparently unrelated to its psychedelic properties. Its low potency is probably responsible for its relative neglect by recreational substance users, as the successful search for structure-activity relationships in the hallucinogen field focused largely on finding more potent analogues. Renewed interest in the possible therapeutic applications of psychedelic drugs may hopefully lead to novel insights regarding the commonalities and differences between the actions of individual classic hallucinogens. Copyright © 2018 American Chemical Society.